Paradoxical role of an Egr transcription factor family member, Egr2/Krox20, in learning and memory - Poirier, Roseline; Cheval, Hélène; Mailhes, Caroline; Charnay, Patrick; Davis, Sabrina; Laroche, Serge (Frontiers in Behavioral Neuroscience, 2007)
It is well established that Egr1/zif268, a member of the Egr family of transcription factors, is critical for the consolidation of several forms of memories. Recently, the Egr3 family member has also been implicated in learning and memory. Because Egr family members encode closely related zinc-finger transcription factors sharing a highly homologous DNA binding domain that recognises the same DNA sequence, they may have related functions in brain. Another Egr family member expressed in brain, Egr2/Krox20 is known to be crucial for normal hindbrain development and has been implicated in several inherited peripheral neuropathies; however, due to Egr2-null mice perinatal lethality, its potential role in cognitive functions in the adult has not been yet explored. Here, we generated Egr2 conditional mutant mice allowing postnatal, forebrain-specific Cre-mediated Egr2 excision and tested homozygous, heterozygous and control littermates on a battery of behavioural tasks to evaluate motor capacity, exploratory behaviour, emotional reactivity and learning and memory performance in spatial and non-spatial tasks. Egr2-deficient mice had no sign of locomotor, exploratory or anxiety disturbances. Surprisingly, they also had no impairment in spatial learning and memory, taste aversion memory or fear memory using a trace conditioning paradigm. On the contrary, Egr2-deficient mice had improved performance in motor learning on a rotarod, and in object recognition memory. These results clearly do not extend the phenotypic consequences resulting from either Egr1 or Egr3 loss-of-function to Egr2. In contrast, they indicate that Egr family members may have different, and in certain circumstances antagonistic functions in the adult brain.